Fitness cost of incubation in great tits (Parus major) is related to clutch size - de Heij, Maaike E (The Royal Society, 2006)
Life-history theory predicts that parents produce the number of offspring that maximizes their fitness. In birds, natural selection on parental decisions regarding clutch size may act during egg laying, incubation or nestling phase. To study the fitness consequences of clutch size during the incubation phase, we manipulated the clutch sizes during this phase only in three breeding seasons and measured the fitness consequences on the short and the long term. Clutch enlargement did not affect the offspring fitness of the manipulated first clutches, but fledging probability of the subsequent clutch in the same season was reduced. Parents incubating enlarged first clutches provided adequate care for the offspring of their first clutches during the nestling phase, but paid the price when caring for the offspring of their second clutch. Parents that incubated enlarged first clutches had lower local survival in the 2 years when the population had a relatively high production of second clutches, but not in the third year when there was a very low production of second clutches. During these 2 years, the costs of incubation were strong enough to change positive selection, as established by brood size manipulations in this study population, into stabilizing selection through the negative effect of incubation on parental fitness.